PERAN PENGALAMAN KERJA DAN MOTIVASI TERHADAP PRESTASI KERJA PEGAWAI DINAS KELAUTAN, PERIKANAN DAN KETAHANAN PANGAN KABUPATEN MANGGARAI - Margareta Gonda Neon; Sayekti Suindyah; Endah Budiarti (Fakultas Ekonomi Universitas 45 Surabaya, 2021)
This type of research is explanatory research, the approach approach uses a quantitative approach, and data analysis uses SPSS. The research sample was 35 employees. The aims of this research are 1). To find out the description of the object/subject of research. 2). To test and analyze the relationship of the effect of work experience on the work performance of the employees of the Department of Marine Affairs, Fisheries and Food Security, Manggarai Regency. 3). To test and analyze the relationship of the influence of motivation on the work performance of the employees of the Department of Marine Affairs, Fisheries and Food Security, Manggarai Regency. The results showed that: 1). Simultaneously, work experience and motivation have a significant effect on increasing the work performance of employees of the Department of Marine Affairs, Fisheries and Food Security, Manggarai Regency, showing the calculated F value is 2,005 with a significance level known from the sig value of 0.002 (smaller than 0.05). . 2). Partially, work experience and motivation have a significant effect on increasing the work performance of the Manggarai Regency Marine, Fisheries and Food Security Service employees, based on the t test results, it is known that work experience has a dominant effect on the work performance of the Manggarai Regency Marine, Fisheries and Food Security Service employees; evidenced by the value of t count is 1,400 with a significance level of 0.003 (smaller than 0.05).